Clinical features and gene variation analysis of COQ8B nephropathy: Report of seven cases - Liang, Rui; Chen, Xuelan; Zhang, Ying; Law, Chak-Fun; Yu, Sijie; Jiao, Jia; Yang, Qin; Wu, Daoqi; Zhang, Gaofu; Chen, Han; Wang, Mo; Yang, Haiping; et al. (Frontiers in Pediatrics, 2023)
Abstract Objective: COQ8B nephropathy is a relatively rare autosomal recessive kidney disease characterized by proteinuria and progressive deterioration of renal function and eventually leading to end-stage renal disease (ESRD). The objective is to study the characteristics and correlation between the genotype and clinical phenotype of COQ8B nephropathy. Methods: This is a retrospective study focusing on the clinical characteristics of 7 COQ8B nephropathy cases diagnosed by gene sequencing. The patients’ basic information, clinical manifestations, examinations, imaging, genomes, pathology, treatments, and prognosis were reviewed. Results: Of the 7 children, there were 2 males and 5 females. The median age at the disease onset was 5 years and 3 months. The initial main clinical manifestations were proteinuria and renal insufficiency. Among them, 4 had severe proteinuria, 4 had focal segmental glomerulosclerosis (FSGS) diagnosed by renal biopsy, and 2 showed nephrocalcinosis by ultrasound. There were no other clinical manifestations in all 7 cases (such as neuropathy, muscle atrophy, etc.). The gene mutations in the 7 cases were all exon variants, which were classified as heterozygous or homozygous variants by family verification analysis. Compound heterozygous variants were predominant in all the cases, and all gene variants were inherited from their parents. One novel mutation, c.1465c>t, was found in this study. This gene mutation resulted from changing in the amino acid sequence, thus responsible for the abnormal protein structure. 2 cases with early diagnosis of COQ8B nephropathy presented with no renal insufficiency were treated with oral coenzyme Q10 and they maintained normal renal function. Among the other 5 cases who were treated with coenzyme Q10 after renal insufficiency, the deterioration of renal function could not be reversed and they progressed to ESRD within a short time (median time: 7 months). Follow-up of those renal transplantation cases showed normal renal function with coenzyme Q10 supplement. Conclusion: For unexplained proteinuria, renal insufficiency or steroid-resistant nephrotic syndrome, gene sequencing should be considered in addition to renal biopsy as soon as possible. Early diagnosis of COQ8B nephropathy and early supplementation of sufficient coenzyme Q10 can control the progression of the disease and significantly improve the prognosis.